RELIGIOUS IDENTITY AS PERFORMANCE: MUSLIM WOMEN, VISUAL CULTURE, AND PLATFORM LOGICS ON INSTAGRAM IN KAZAKHSTAN - Umbet R.S. (Scientific Results, 2026)
This study explores how Muslim women in Kazakhstan construct and perform religious identity on Instagram through visual practices, emotional narratives, and everyday lifestyle representations. Using qualitative content analysis, four anonymized public profiles were examined to identify dominant patterns of digital religious self-presentation. The findings reveal that religious identity is embedded in family roles, motherhood, emotional expression, modest fashion, entrepreneurial self-branding, and collective female rituals rather than articulated primarily through explicit theological discourse. Instagram functions not only as a site of representation but as a performative environment where piety, femininity, and social belonging are negotiated through platform-specific aesthetics and algorithmic visibility. The analysis identifies four overlapping models of Muslim femininity: domestic care-oriented piety, emotionally expressive family-centered religiosity, entrepreneurially framed religious leadership, and community-based sisterhood-oriented devotion. These models demonstrate that digital religious identity is dynamic, situational, and shaped by social roles, audience expectations, and platform logics. By focusing on a Central Asian context, the study contributes regionally grounded insights into gendered digital religiosity in post-Soviet Muslim societies and extends current theoretical debates on religious identity as a performative and technologically mediated practice